Oral health in obese children common findings, prevention, treatment, and outcome - Salmin, Rana S.; Bin-Saeed, Wael S.; Albakr, Reem A.; Alkhalid, Nouf I.; Alqahtani, Noura S.; Alwahib, Rana A.; Arab, Ali S.; Alhazmi, Sarah F.; Alharbi, Doaa M.; Alotaibi, May M. (International Journal Of Community Medicine And Public Health, 2024)
Childhood obesity is a significant global public health issue, closely linked to various oral health challenges, including dental caries, periodontal disease, and malocclusion. Obese children are more prone to these dental problems due to dietary habits that include high sugar and carbohydrate intake, poor oral hygiene practices, and systemic inflammation. This review explores the common oral health issues faced by obese children and emphasizes the importance of preventive strategies and tailored treatment approaches. Preventive measures include promoting healthy dietary habits, improving oral hygiene practices, and ensuring regular dental check-ups. Dietary modifications, such as reducing the intake of sugary snacks and beverages, play a crucial role in preventing tooth decay and other dental problems. Educating children and caregivers about proper brushing and flossing techniques and the use of fluoride toothpaste and dental sealants further supports oral health. Regular dental visits allow for early detection and management of dental issues, with professional cleanings, fluoride treatments, and appropriate restorative and periodontal therapies being integral components of care. The outcomes of these comprehensive treatment strategies are generally positive, leading to improved oral health and overall quality of life for obese children. Multidisciplinary collaboration among healthcare providers, including dentists, pediatricians, and nutritionists, is essential to develop effective care plans that address both obesity and oral health. This integrated approach ensures that obese children receive holistic care that promotes lifelong healthy habits, reducing the risk of future dental and systemic health problems. The review underscores the necessity of a concerted effort to address the intertwined issues of obesity and oral health in children, highlighting the potential for significant health improvements through targeted prevention and treatment strategies.